Assessment on Corrosion Damage of Steel Reinforced Concrete Structures of Kathmandu Valley Using Corrosion Potential Mapping Method - Phulara, Nav Raj; Bhattarai, jagadish (Journal of the Institute of Engineering, 2019)
Present study is focused to investigate the corrosion damage conditions of steel reinforced twenty eight different types of the concrete structure samples from Kathmandu valley using a non-destructive technique of the corrosion potential mapping (CPM) method in accordance with ASTM C876-91 Standards. It is found from the present assessment that the building roof of public owners house, hume pipes and building pillars used in Kathmandu valley are generally under the low risk of reinforced steel corrosion in these concrete structures, that is, less than 10 % probability of the corrosion damage, although the fencing pillars and the roof slabs of different office buildings are found to be high risk of reinforced steel corrosion damage, that is, more than 90 % probability of corrosion damage among twenty eight concrete structures.